Application of Taguchi method in the optimization of biodiesel production from waste cooking oil using MoO3/SiO2 catalysts - Anwar, Nur Sharina (2012)
Today, edible oil or cooking oil is one of the most important elements in food production industry as well as food preparation at home. As a consequence, large amount of waste cooking oil (WCO) was produced especially in developing countries. With increasing fossil fuel price and decreasing renewable energy supply, it is of main interest to utilize the WCO by converting it into usable and beneficial product which is biodiesel. Heterogeneous acid catalyst which can simultaneously carry out esterification and transesterification reaction was selected for converting that kind of low grade oil into biodiesel. In this study, sulfated MoO3/SiO2 with different loading percentage of MoO3 were synthesized via impregnation method and applied in the transesterification reaction of WCO to biodiesel. X-ray Diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area and Ammonia-Temperature Programme Desorption (NH3-TPD) were used to characterize the catalysts synthesized while the biodiesel produced were analyzed by proton Nuclear Magnetic Resonance (1H NMR) and Gas Chromatography-Flame Ionization Detector (GCFID). The transesterification reaction was optimized by Taguchi method in which L16 orthogonal array involving four levels and five parameters was employed to investigate the effect of each reaction parameters which are reaction temperature, reaction time, methanol to WCO molar ratio, catalyst amount and MoO3 loading on SiO2 and imultaneously determine the optimum conditions for the transesterification reaction. Results showed that the reaction temperature, reaction time, methanol to WCO molar ratio and catalyst amount were the significant influential parameters that influence the final yield of biodiesel while MoO3 loading on SiO2 is insignificant parameter. The optimum conditions of the reaction were derived to be at 453 K reaction temperature, 6 h reaction time, 30:1 methanol to WCO molar ratio, 1 wt% of the catalyst amount and 3 wt% MoO3 loading on the SiO2 with 98.56 % biodiesel yield obtained which matched well with predicted yield. Some of physicochemical properties of the biodiesel produced were analyzed and the results were complied with the international standard specification requirements. Another study on the catalyst performance shows that the catalyst exhibits good stability and reusability up to at least five times in transesterification reaction without significant lost in activity. The overall results indicate the biodiesel produced exhibits good properties and suitability to be produced industrially.